2019
DOI: 10.1002/bse.2296
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally sustainable or economically sustainable? The effect of Chinese manufacturing firms' corporate sustainable strategy on their green performances

Abstract: Environmentally and economically sustainable strategies are predicted to influence the public perception of a firm's green performance in terms of environmental protection as well as corporate social responsibility as a whole. We empirically tested this prediction with the data from 214 Chinese manufacturing firms. Our empirical findings showed that firms' environmentally sustainable strategies are more important compared with the economic ones in shaping firms' green performances.Moreover, we also found a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 63 publications
(65 reference statements)
0
45
0
2
Order By: Relevance
“…The results, presented in Table 7, showed that all coefficients were nearly consistent with the regression results found in Table 5. Second, given that firms' sustainability levels are positively related to corporate green image (Yang, Li, Yu, Zeng, & Sun, 2019), we performed a robustness check using “green image” as an alternative to “sustainability performance.” The findings, reported in Tables 8 and 9, were not significantly different from those shown in Tables 5 and 6. Third, we used the Markov chain Monte Carlo (MCMC) estimation method as an alternative to the bootstrap method.…”
Section: Resultsmentioning
confidence: 99%
“…The results, presented in Table 7, showed that all coefficients were nearly consistent with the regression results found in Table 5. Second, given that firms' sustainability levels are positively related to corporate green image (Yang, Li, Yu, Zeng, & Sun, 2019), we performed a robustness check using “green image” as an alternative to “sustainability performance.” The findings, reported in Tables 8 and 9, were not significantly different from those shown in Tables 5 and 6. Third, we used the Markov chain Monte Carlo (MCMC) estimation method as an alternative to the bootstrap method.…”
Section: Resultsmentioning
confidence: 99%
“…However, research in this field is still limited. In particular, little research has focused on the Chinese context, which has experienced rapid economic growth but now faces severe environmental challenges and resource constraints (Yang, Li, Yu, Zeng, & Sun, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that pressures like social, governmental, internal, and external are directly and positively linked to corporate environmental behaviour. Further, Yang, Li, Yu, Zeng, and Sun () found environmental strategy as more useful than economic strategy in order to enhance firm's green performance through an empirical investigation of 214 Chinese manufacturing organizations. Grolleau, Mzoughi, and Sutan () carried out quasi‐experimental test to check whether green advertisement dilutes perceived value of conventional products and found non‐presence of any such behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%